A show of Hands: Novel and conserved expression patterns of teleost hand paralogs during craniofacial, heart, fin, peripheral nervous system and gut development. Issue 12 (16th June 2021) - Reynolds, Samantha; Pierce, Christian; Powell, Benjamin; Kite, Alexandra; Hall‐Ruiz, Nicholas; Schilling, Thomas; Le Pabic, Pierre
Abstract: Background: Hand genes are required for the development of the vertebrate jaw, heart, peripheral nervous system, limb, gut, placenta, and decidua. Two Hand paralogues, Hand1 and Hand2, are present in most vertebrates, where they mediate different functions yet overlap in expression. In ray‐finned fishes, Hand gene expression and function is only known for the zebrafish, which represents the rare condition of having a single Hand gene, hand2 . Here we describe the developmental expression of hand1 and hand2 in the cichlid Copadichromis azureus . Results: hand1 and hand2 are expressed in the cichlid heart, paired fins, pharyngeal arches, peripheral nervous system, gut, and lateral plate mesoderm with different degrees of overlap. Conclusions: Hand gene expression in the gut, peripheral nervous system, and pharyngeal arches may have already been fixed in the lobe‐ and ray‐finned fish common ancestor. In other embryonic regions, such as paired appendages, hand2 expression was fixed, while hand1 expression diverged in lobe‐ and ray‐finned fish lineages. In the lateral plate mesoderm and arch associated catecholaminergic cells, hand1 and hand2 swapped expression between divergent lineages. Distinct expression of cichlid hand1 and hand2 in the epicardium and myocardium of the developing heart may represent the ancestral pattern for bony fishes. Key Findings: hand1 and hand2 are expressed in the developing cichlid heart, paired fins, pharyngeal arches, peripheric nervous system and gut. hand1 alone is expressed in the cichlid lateral plate mesoderm. hand2 alone is expressed in cichlid median fins. hand1 expression is detected in the cichlid epicardium alone, while hand2 is detected only in the myocardium.